2009
DOI: 10.1007/s10995-009-0541-7
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and Vitamin A Status of Pregnant Women in Calabar Urban, Southeastern Nigeria

Abstract: Vitamin A deficiency (VAD) is prevalent in developing countries. Socioeconomic status is increasingly being associated with nutritional status of individuals. Efforts to control or eliminate VAD must focus on socioeconomic factors and how to tackle them in the midst of other well recognized strategies. This research sought to determine the socioeconomic factors that may affect the serum retinol levels of pregnant women in Calabar, Nigeria. A total of 101 pregnant women in Calabar were studied for the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
2
12
1
Order By: Relevance
“…The findings reported here are similar to those found in China, where a frequency of VAD of 5.2% was found in a group of 1209 pregnant women evaluated in 150 urban or rural areas between 2013 and 2014 [30]. Compared to the present findings, other studies conducted in developing countries using the cut-off point of <0.70 μmol/L reported much higher prevalence rates of VAD in pregnant women: 24.6% in 3270 pregnant women in Iran [31], 20% in a sample of 80 women in Egypt [32], 18.5% in 200 women in Bangladesh [33], 15.8% in 101 women in Nigeria [34], 13.8% in 738 women in Guinea-Bissau [35], and 10.6% in 160 pregnant adolescents in Venezuela [18]. However, only the sample sizes used in the studies conducted in China, Iran, and Guinea-Bissau were large enough to yield robust data.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The findings reported here are similar to those found in China, where a frequency of VAD of 5.2% was found in a group of 1209 pregnant women evaluated in 150 urban or rural areas between 2013 and 2014 [30]. Compared to the present findings, other studies conducted in developing countries using the cut-off point of <0.70 μmol/L reported much higher prevalence rates of VAD in pregnant women: 24.6% in 3270 pregnant women in Iran [31], 20% in a sample of 80 women in Egypt [32], 18.5% in 200 women in Bangladesh [33], 15.8% in 101 women in Nigeria [34], 13.8% in 738 women in Guinea-Bissau [35], and 10.6% in 160 pregnant adolescents in Venezuela [18]. However, only the sample sizes used in the studies conducted in China, Iran, and Guinea-Bissau were large enough to yield robust data.…”
Section: Discussioncontrasting
confidence: 69%
“…The lack of any statistically significant association was probably due to the small number of women in each of the strata compared; therefore, these results need to be taken merely as an indication. However, likewise, other studies have reported lower serum retinol levels with increased parity [30,34,51,56]. This could be explained by the fact that repeat pregnancies reduce or deplete maternal stocks of nutrients [56].…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, El-Khashab et al (2013) found that 20% of pregnant women had VAD [15]. In other developing countries, VAD was found among 15.8% (in Nigeria) and 18.8% (in Bangladesh) of pregnant women [16, 17]. The frequency of mothers with retinol intake below the recommended intake (70%) is higher than that reported from other developing countries (53%) [17].…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya in 2007, 33.3% of pregnant women had a retinol rate < 0.7 μmol/L at the 36th week of amenorrhea [10]. In Nigeria, only 36.5% of women out of 101 had normal retinol in 2011 [6]. In Bangladesh, more than half of women out of 200 have a low rate of retinol, and 18.5% of them are deficient in Vitamin A [8].…”
Section: Discussionmentioning
confidence: 99%